Adaptive backstepping controller design of quadrotor biplane for payload delivery. Issue 12 (2nd February 2022) - Dalwadi, Nihal; Deb, Dipankar; Muyeen, S. M.
Abstract: Performance of the UAVs for a particular application can be enhanced by hybrid design, where take‐off, hover, and landing happen like rotary‐wing UAVs, and flies like fixed‐wing UAVs. A backstepping controller and an adaptive backstepping controller are designed for trajectory tracking and payload delivery in a medical emergency or medical substance delivery like vaccine delivery in the presence of wind gust. Simulation results show that the backstepping controller effectively tracks the trajectory during the entire flight envelope, including take‐off, hovering, the transition phase, level flight mode, and landing. A comparison between Backstepping, Integral Terminal Sliding Mode (ITSMC) and Adaptive Backstepping controllers for payload delivery show that the adaptive backstepping controller effectively tracks the altitude and attitude. ITSMC is capable of tracking the desired trajectory for a change in the mass but has sluggish response. The backstepping controller generates a steady‐state error in altitude during the mass change in biplane quadrotor.